GeoGebra AR in Mathematics Learning: Students’ Perceptions from Indonesian Junior High Schools - Angre Andes Thofan; Putri Sasalia S.; Loy Cindy Br Milala (Pendidikan Matematika STKIP Kusuma Negara, 2025)
It is becoming more and more necessary for educational practices to use digital technologies that can facilitate efficient and meaningful learning in the age of rapid technology advancement. Digital technology is crucial in mathematics education because it helps pupils envision and comprehend abstract ideas that are frequently challenging to learn through traditional teaching methods. The purpose of this study is to examine students’ views on the use of GeoGebra Augmented Reality (AR) in mathematics classes at public junior high schools in Palangka Raya. Twenty questions covering five areas—knowledge and awareness, usefulness and application, obstacles and restrictions, support and facilities, and interest and attitude—were answered by 248 students using a survey method with a descriptive quantitative approach. The findings indicate that students’ overall perceptions of GeoGebra AR are high, especially regarding its usefulness, their interest in it, and the support from their schools. They still have to deal with issues like device availability and restricted internet access, though. In conclusion, GeoGebra AR has great potential as an innovative learning tool to boost students’ motivation and understanding of math, in line with the Merdeka Curriculum.